Gamma-Maxwell distribution. Issue 9 (3rd May 2017) - Iriarte, Yuri A.; Astorga, Juan M.; Bolfarine, Heleno; Gómez, Héctor W.
ABSTRACT: A new two-parameter distribution, the gamma-Maxwell distribution, isproposed and studied. We generate the new distribution using the gamma-G generator of distributions. The proposal distribution can be seen as an extension of the Maxwell distribution with more flexibility in terms of the distribution asymmetry and kurtosis. We study some probability properties, discuss maximum-likelihood estimation and present a real data application indicating that the new distribution can improve the ordinary Maxwell distribution in fitting real data.